Pelatihan petani peternak di SD Inpres Benteng II Kabupaten Kepulauan Selayar - Rosdiana Ngitung (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The majority of people in Benteng Village, SelayarRegency work as farmers and breeders. The problem faced bythe community (broiler breeder families) is the management ofthe chicken business that is still weak, especially broilerlivestock and inadequate management and ration availability.The solution offered through this service program wasintended to train farmers in Benteng Village about how toimprove the management of the chicken business, as well asthe management and manufacture of chicken rations,especially for chicken broilers. The target group of thisprogram was the chicken farmers. The activities consisted ofprovidingan understanding to farmers in terms of improvinginsight, knowledge, ability, skills, and confidence in compilingbroiler rations that will produce broilers that are low in fat andcholesterol. The method used in this training was to conductcounseling in the form of presentations and question andanswer, conduct training for participants in preparing broilerrations, and conduct discussions with participants to resolverelated issues regarding broiler feed that will produce low fatand cholesterol broilers. The community service program alsoinvolved partner institutions, the Government of SelayarIslands Regency and Community Leaders in Benteng District.